Emergence of mcr-1 mediated colistin resistant Escherichia coli from a hospitalized patient in Bangladesh - Refath Farzana; Lim S Jones; Md. Anisur Rahman; Mark A Toleman; Kirsty Sands; Edward Portal; Ian Boostrom; Md. Abul Kalam; Brekhna Hassan; AKM Nasir Uddin; Timothy R Walsh (Journal of Infection in Developing Countries)
Introduction: The emergence of plasmid mediated mcr in bacteria has become global public health threat. Herein, we report a mcr-1 positive E. coli in normal human flora from a patient admitted in Dhaka Medical College Hospital (DMCH).